Tekanan Fiskal dan Keberlanjutan Penganggaran Modal pada Sektor Pemerintah: Pendekatan Tinjauan Literatur Sistematis - Lilis Marlina; Fifi Yusmita; Syukrie Abdullah (Organum: Jurnal Saintifik Manajemen dan Akuntansi, 2023)
Fiscal stress faced by local governments over the years can be a threat to the sustainability of capital budgeting in providing public goods and services. The purpose of the research is to map the trends of scientific publications and the most prominent types of research, and to synthesize research results on the relationship between capital budgeting practices and fiscal stress in the government sector. The method be elected in this study is a systematic literature review with reviews and analyzes systematically the effect of fiscal stress on the sustainability of capital budgeting published in reputable international journals indexed by Scopus. Based on the results of the study, it was found that: first, the first research on the relationship between capital budgeting and fiscal stress was carried out in the 1980-1989 time period. Then research on this topic is increasing in the period 2000-2020. Second, the most dominating type of research is quantitative (63%). While the remaining 37% are qualitative studies. Third, the development of research results on the relation among capital budgeting and fiscal stress in the government sector still gives different responses among researchers. This study contributes to providing a comprehensive review of the development capital budgeting research in a situation where the government is facing fiscal stress, and is useful for practitioners in allocating resources for the sustainability of capital budgeting in the government sector.